Incorrigible - Demerson, Velma, 1920-2019. (Waterloo, Ont. : Wilfrid Laurier University Press, 2004)
"On a May morning in 1939, eighteen-year-old Velma Demerson and her lover were sharing breakfast when the police arrived to take her away. Her "crime," loving a Chinese man, was compounded by her pregnancy and subsequent mixed-race child. Sentenced to a home for wayward girls, Ms. Demerson was soon transferred, together with forty-six other young women, to Toronto's Mercer Reformatory for Females." "Locked in their cells for twelve hours a day and compelled to work in the on-site laundry and factory, they also endured repeated suspect medical examinations. When Velma Demerson was eventually released after ten months' incarceration, weeks of solitary confinement, abusive medical treatments, and the state's apprehension of her child, her marriage to her lover resulted in the loss of her citizenship status." "Incorrigible is a survivor's story. It is the story of how Ms. Demerson, and many other women, were classified and condemned as criminals or as mentally "defective," when their choice of lover may have been their worst crime."--Jacket
CHAPTER 1; CHAPTER 2; CHAPTER 3; CHAPTER 4; CHAPTER 5; CHAPTER 6; CHAPTER 7; CHAPTER 8; CHAPTER 9; CHAPTER 10; CHAPTER 11; CHAPTER 12; CHAPTER 13; CHAPTER 14; CHAPTER 15; CHAPTER 16; CHAPTER 17; CHAPTER 18; AFTERWORD; NOTES; ACKNOWLEDGEMENTS
Print version record.
Includes bibliographical references.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Demerson, Velma, -- 1920-2019.; Demerson, Velma, -- 1920-; Demerson, Velma, -- 1920-2019; Women prisoners -- Ontario -- Biography; Interracial dating -- Ontario; Amours interraciaux -- Ontario; Prisonnières -- Ontario -- Biographies; SOCIAL SCIENCE -- Penology; BIOGRAPHY & AUTOBIOGRAPHY -- Social Scientists & Psychologists; Interracial dating; Women prisoners; Ontario; BIOGRAPHY & AUTOBIOGRAPHY; Demerson, Velma; Interracial dating; Penology; SOCIAL SCIENCE; Social Scientists & Psychologists; Women prisoners; Biographies; Biographies; Biographies